Capacity of astrocytes to promote axon growth in the injured mammalian central nervous system - Hemati-Gourabi, Matin; Cao, Tuoxin; Romprey, Megan K.; Chen, Meifan (Frontiers in Neuroscience, 2022)
Understanding the regulation of axon growth after injury to the adult central nervous system (CNS) is crucial to improve neural repair. Following acute focal CNS injury, astrocytes are one cellular component of the scar tissue at the primary lesion that is traditionally associated with inhibition of axon regeneration. Advances in genetic models and experimental approaches have broadened knowledge of the capacity of astrocytes to facilitate injury-induced axon growth. This review summarizes findings that support a positive role of astrocytes in axon regeneration and axon sprouting in the mature mammalian CNS, along with potential underlying mechanisms. It is important to recognize that astrocytic functions, including modulation of axon growth, are context dependent. Evidence suggests that the local injury environment, neuron-intrinsic regenerative potential, and astrocytes’ reactive states determine the astrocytic capacity to support axon growth. An integrated understanding of these factors will optimize therapeutic potential of astrocyte-targeted strategies for neural repair.